The mediating role of total quality management between the entrepreneurial orientation and the organizational performance - Al-Dhaafri, Hassan Saleh; Al-Swidi, Abdullah Kaid; Yusoff, Rushami Zien (Emerald Group Publishing Limited, 2016)
Purpose– The purpose of this paper is to examine the joint effect of entrepreneurial orientation (EO) and total quality management (TQM) on the organizational performance.In addition, this study aimed to examine the ability of TQM to transmit the effect of EO on the organizational performance.Design/methodology/approach– To examine the hypothesized model of the study, the survey questionnaire research design was employed. The data were collected from Dubai police department.The total number of questionnaires distributed was 320 out of which only 111 usable questionnaires were returned.The structural equation modeling partial least squares approach was used.Findings– The statistical results confirmed the effect of EO and TQM on the organizational performance.In addition, TQM was found to partially mediate the effect of EO on organizational performance.Practical implications – Further details and valuable implications of this study were discussed throughout the study. The results of this study have many practical implications.The results will help managers to make the proper decisions when deciding to implement TQM in their organizations.TQM can help managers with strong EO to achieve maximum performance in organizations and to remain competitive in the market.Originality/value – This study is a rare and unique empirical study that examines the effect of EO on TQM and the mediating effect of TQM on the EO-performance relationship.